EFEKTIVITAS PELAYANAN ADMINISTRASI PEMERINTAH KECAMATAN SETU KABUPATEN BEKASI - Ishma Ratu Genia; Evi Priyanti; Rahman Rahman (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This research is motivated by the fact that public administrative services in Setu District, Bekasi Regency, still face various problems despite the Community Satisfaction Index (IKM) showing a very good category. The study aims to examine and analyze the effectiveness of administrative services in Setu District Government using Sondang P. Siagian’s effectiveness theory (time, accuracy, and service style) along with an additional indicator of service facilities. The research method employed is descriptive qualitative. The findings indicate that administrative services have made efforts to improve effectiveness through the implementation of SOPs, complaint channels, and staff training. However, several obstacles remain, including manual queuing systems that hinder time efficiency, minor errors in documents, and inconsistent attitudes of staff toward service users. Furthermore, basic service facilities are available but remain inadequate in terms of quality and accessibility. Thus, the effectiveness of administrative services in Setu District has shown progress, yet continuous improvements are still needed, particularly regarding accuracy, service style, and infrastructure provision. Keywords: Effectiveness, Administrative Services, District Government